Financial Innovation and Its Effect on Financial Performance: The Case of Commercial Bank of Ethiopia, Nekemte Town Branches - Gudata Abara Chali (The Indonesian Institute of Science and Technology Research, 2026)
This study examines the effect of financial innovation on the financial performance of the Commercial Bank of Ethiopia (CBE) in Nekemte Town. As banking shifts toward revenue-oriented digital strategies, identifying high-impact technologies is essential. A census survey of 56 branch managers and vice-managers from ten branches was analyzed using Pearson correlation and multiple regression (SPSS 26). Five innovation dimensions were evaluated: product innovation, process innovation, mobile banking, technology transfer, and remittance technology. Findings reveal that remittance technology is the strongest predictor of financial performance (β = 0.661, p < 0.01), followed by process innovation (β = 0.213) and mobile banking (β = 0.193). The regression model explains 92.7% of performance variance (R² = 0.927), indicating substantial explanatory power. The results suggest that profitability in regional markets depends largely on efficient payment and fund transfer systems. The study recommends expanding digital onboarding services and exploring blockchain solutions to reduce transaction costs and strengthen competitive advantage.